Exploring the Professional Development Needs of International School Principals in the UAE - Alkutich, Mohamad (2021)
School leadership is considered to be a significant part of domestic and international affairs. Effective school principal who can effectively represent the school, build the students as well as the teachers, and lead a formidable educational team is the dream of every nation. The case study of leadership development training for international school principals in the UAE was chosen in this research, and the primary objective was to evaluate international school principals to obtain their impressions of their professional learning activities. The technique used in this research was a mixed-method approach, which gave a clearer picture of the impressions gained from international school principals of leadership development training. A survey framework was used in the quantitative approach accompanied by a qualitative research interview to assess their views on their professional preparedness. The nine principal of international schools expressed an interest in attending the interview process among these 59 international schools in the UAE. Participants ' perceptions support four leading leadership practices: vision and direction understanding and development of individuals, organizational progress, and management of learning and teaching programs. The Participating Principals demonstrated a human-centred approach, focusing on capacity building, developing positive relationships as well as an active duty of care. Further, the effectiveness of the Professional Development program was not worthwhile considering that principals were not invited to give their views on the matters of development. The reflections and narratives of Principals provided valuable data for exploration and conceptualization. The findings of this research are significant, and it adds more rich contributions to the body of knowledge on the learning learning and development of international school principalship.